FOOD AND FEEDING HABITS OF PENAEUS SEMISULCATUS DE HAAN AT MANDAPAM - Thomas, M M (Indian Journal of Fisheries, 2011)
Penaeus semisulcatus feed on a variety of food items viz., polyohaetes, crustaceans,molloiscs diatoms, foraminiferEns and radiolarians, eventhough, detritusand sand formed bulk of the stpmaoh contents. There was marked difference in thefood composition of the species from the Palk Bay and Gulf of Mannar. Activelyfed prawns were found to be more in the night catches. The species do not exhibitpreference to any particular food itÂ«m. It is concluded that the abundance of aparticular food item was dependent on its availability during the season when theyare predominent. There was no significant difference in the food and fee^ding habitsin the various size groups